Effect of B2O3 Content on the Sintering Basic Characteristics of Mixed Ore Powder of Vanadium-Titanium Magnetite and Hematite - Hao Liu; Ke Zhang; Qingfeng Ling; Yuelin Qin (Journal of Chemistry)
The sintering basic characteristics of iron ore play a key role in the process of sintering. In this study, the effects of B2O3 on the assimilation characteristics, softening temperature, fluidity of liquid phase, compressive strength of bonding phase, and microstructure of the mixed fine powder of hematite and vanadium-titanium magnetite (H-VTM) are studied. Results show that B2O3 content from 0%–5% (wt%) could improve the assimilation characteristics of the H-VTM and increase the amount of the liquid phase. The liquidity of the bonding phase index (LBPI) of the H-VTM increases from 3.7 to 24.2. When B2O3 content exceeds 2%, the diameter of the pore in the H-VTM sintered samples enlarges. However, the compressive strength gradually decreases. Boron and calcium-magnesium-aluminium elements are abundant in the bonding phase, which can reduce the formation of calcium silicate and perovskite in H-VTM sintered samples.